One Party, Two Systems: Corruption in the People’s Republic of China and Attempts to Control It - Kolenda, Helena (Columbia Journal of Asian Law, 1990)
In 1989, 70 years after the May Fourth Movement and 40 years after the founding of the People’s Republic of China (PRC), students took to the streets of urban China as they did in 1919 to protest the state of the nation. A major grievance of the students and their sup- porters was corruption. According to an early 1989 survey by the Chinese Academy of Social Sciences and the State Statistical Bureau, many Chinese regarded corrupt behavior of public officials as one of the major threats to social order.1 Tragically, the public outcry against corruption and for greater democracy that was centered around Tian’anmen Square was itself branded by the Chinese Communist Party (Party) as the true threat to social order. The tanks and guns of June 4, 1989 (June 4th) were the Party’s response. One of the major pledges the Party made to the Chinese people when it came to power in 1949 was to end the corruption that had plagued the country during the predecessor Nationalist regime. In the ensuing 40 years, the Party has launched numerous campaigns to purify its own ranks as well as those of the government it controls, yet now the Party itself stands condemned, even by its own admission. Some have said that the violent measures of June 4th exemplify the Party’s tactic of “killing the chickens to frighten the monkeys” to ensure a docile population. In the aftermath of June 4th, however, the Party is also running scared. The PRC leadership has been unsuccessful in meaningfully curb- ing corruption. This article begins with a general consideration of corruption as a predicament for all countries, but especially for the developing world. It then looks at factors in the PRC, both cultural and institutional, that encourage corrupt behavior. The final sections introduce PRC responses to the problem, legislative and otherwise, and offer some comments on the likelihood of their success.